Determinants Of Tourism Village Development On Communitywelfare In Tabanan District - I Putu Herry Mahendra Putra; Made Suyana Utama (Universitas Udayana, 2025)
The tourism is one of the sources of foreign exchange income for a country. One of the provincesin Indonesia that has the largest tourism-leading sector is Bali Province. Through the developmentof tourism villages and community-based tourism, it is expected to improve the communitywelfare. This Study aimed to analyze the effect of community participation, government role, andcommunity empowerment on tourism village development and community welfare in TabananRegency. The population of this study is the community involved in tourism village developmentin Tabanan Regency, namely Pinge Tourism Village and Jatiluwih Tourism Village. The samplingtechnique used was non-probability sampling with a purposive sampling technique, and weobtained a sample of 138 observational samples. Data analysis techniques were used in the studyusing a structural equation model (SEM) with partial least squares (PLS) software. The analysisresults show that community participation, government role, and community empowermentpositively and significantly affect community welfare through tourism village development inTabanan Regency. The community and government can maintain tourism village development toimprove the welfare of rural communities and the facilities needed to meet the needs of touristvillages.